PELUANG PEMBANGUNAN MUSEUM LADA DI LAMPUNG UTARA - Adi Asmariadi Budi; Gita Paramita Djausal; M. Hanif Khairy Vidiantara; Henita Astuti (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2021)
North Lampung is famous for its black pepper since the 19th century. In addition, North Lampung is the second largest producer of pepper in Indonesia. Through the analysis of the external environment and also the power possessed by North Lampung, it is necessary to map the opportunities for the construction of the Pepper Museum in North Lampung. This is confirmed by the establishment of Kupi Lado Centrum in 2019 as a branding that became the local identity of North Lampung. Mapping this opportunity based on the accessibility of North Lampung Regency, the tourism market of Lampung Province, and the advantages of Lampung black pepper commodities. The urgency of the construction of a pepper museum in North Lampung Regency is driven by the existence of pepper commodities which are other district commodities in Lampung Province. ABSTRAK Lampung Utara terkenal dengan lada hitam sejak abad ke 19. Selain itu, Lampung Utara merupakan penghasil lada kedua terbesar di Indonesia. Melalui analisis lingkungan eksternal dan juga kekuatan yang dimiliki oleh Lampung Utara, maka perlu dipetakan peluang pembangunan Museum Lada di Lampung Utara. Hal ini ditegaskan dengan pencanangan Kupi Lado Centrum pada 2019 sebagai branding yang menjadi identitas kelokalan Lampung Utara. Pemetaan peluang ini berdasarkan aksesibilitas Kabupaten Lampung Utara, pasar pariwisata Provinsi Lampung, dan keunggulan komoditas lada hitam Lampung. Adapun urgensi pembangunan museum lada di Kabupaten Lampung Utara didorong oleh keberadaan komoditas lada yang merupakan komoditas kabupaten lain di Provinsi Lampung.